Implementation of Information Systems in PT Terminal Teluk Lamong: Does Supply Chain Intervenes? - Baling kustriyono; Indrianawati Usman; Nurullaily Kartika; Vanesia Nadya (International Journal of Supply Chain Management, 2020)
This study examines the effect of information quality and service quality on the organizational impact of implementing information systems at PT Terminal Teluk Lamong. PT Teluk Lamong terminal is the first terminal port in Indonesia that uses a semi-automated concept, so research on this information system is important to do. This study uses a test tool in the form of Smart PLS to see the results of the outer model and the inner model, which in turn will produce relationships between variables. Supply chain management significantly and positively mediates between quality system, information quality, service quality, and organizational impact. Data is collected by distributing questionnaires to all company employees. Of the total 260 employees, only 101 employees of PT Terminal Teluk Lamong participated in filling out the questionnaire given. The participants represented a total of 9 departments in the company. The results found in this research are that there is a significant relationship between the information quality and service quality variables on organizational impact. This research will be used as an evaluation material for the management of PT Terminal Teluk Lamong to update on the implementation of the company's information system.